2022
DOI: 10.1097/qad.0000000000003315
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the coronavirus disease 2019 pandemic on prescriptions for antiretroviral drugs for HIV treatment in the United States, 2019–2021

Abstract: Objective:To assess disruption in healthcare services for HIV treatment by national emergency in response to the coronavirus disease 2019 (COVID-19) pandemic in the United States.Design:Time-series analysisMethods:We analyzed the IQVIA Real World Data–Longitudinal Prescriptions Database and calculated time trends in the weekly number of persons with active antiretroviral prescriptions for HIV treatment, and of persons who obtained antiretroviral prescriptions during January 2017–March 2021. We used interrupted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Our overall results generally comport with three studies considering individual HIV services, especially on the much smaller impact on ART than other services, as expected given that they involve the same data sources [18][19][20]. However, our comparison of two cities allows…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our overall results generally comport with three studies considering individual HIV services, especially on the much smaller impact on ART than other services, as expected given that they involve the same data sources [18][19][20]. However, our comparison of two cities allows…”
Section: Discussionsupporting
confidence: 70%
“…Our main source for PrEP and ART is the IQVIA Real World Data-Longitudinal Prescriptions Database (IQVIA). Methods for extracting prescription counts and defining continuous usage spells vs. new prescriptions have been described previously [18,20]. We consider three measures for PrEP and ART each, by week: number of ongoing prescription spells, number of spells initiated, and number terminated.…”
Section: Iqvia Data (Prep and Art)mentioning
confidence: 99%
“…Similarly, during 2020, the number of persons prescribed PrEP decreased 6% from Q1 (190,955) to Q2 (179,280) but increased to 184,320 in Q3 (2019-2021 EQPC = 3.45%). Following a similar pattern, during 2020, HIV diagnoses decreased 6% from Q1 (8,438) to Q2 (6,228) but increased to 7,905 in Q3 (2019-2020 EQPC = −3.99%). The proportion of persons linked to HIV care, the number who were prescribed ART, and the proportion with a suppressed viral load test result among those tested was stable during the study period.…”
mentioning
confidence: 64%
“…As unemployment increased during the pandemic ( 2 ), many persons lost employer-sponsored health insurance ( 3 ). HIV testing and PrEP prescriptions declined early in the COVID-19 pandemic ( 4 6 ); however, the full impact of the pandemic on use of HIV prevention and care services and HIV outcomes is not known. To assess changes in these measures during 2019–2021, quarterly data from two large U.S. commercial laboratories, the IQVIA Real World Data — Longitudinal Prescription Database (IQVIA), † and the National HIV Surveillance System (NHSS) § were analyzed.…”
mentioning
confidence: 99%
“…The outbreak of COVID-19 in 2020 has significantly disrupted the HIV continuum of care in the United States. Recent work has shown that COVID-19-related disruptions have affected Pre-exposure prophylaxis (PrEP) uptake and adherence [1], antiretroviral therapy (ART) uptake and adherence [2], and HIV testing and care provision [3], [4]. It is therefore not surprising that HIV diagnoses in the United States decreased substantially in 2020, with official data suggesting a drop of approximately 17% from 2019 [5], [6].…”
Section: Introductionmentioning
confidence: 99%